British and Indian Cultural Acculturation Study of Literary Anthropology in White Mughals Novel by William Dalrymple - Dyah Kristyowati (GoAcademica Research & Publishing, 2020)
The study of literary anthropology examines the literary structure in novels, short stories, poems, plays, and, folklore then linked to the concept or context of socio-cultural situations. This research discusses the acculturation of British and Indian cultures in the novel White Mughal. The results of the study found 4 cultural acculturations of British and Indian cultures such as the acculturation of local traditions, buildings, how to dress, and mixed marriages. The backgrounds of cultural acculturation in the novel are economic factors and political factors. This research is library research. The methods used in this research as well as other literary anthropological research focus on cultural acculturation and the factors behind cultural acculturation in this novel.